How to make research information FAIR: DSpace-CRIS and best practices in open research information - Mornati, Susanna (2018)
At 4Science, in DSpace and OJS since2003, in euroCRIS since2010, we contribute to open source projects and participate in international communities, developing and promoting open standards that enable interoperability to make Open Science possible